Influence of liming on residual soil respiration and chemical properties in a tropical no-tillage system - Marcelo,Adolfo Valente (2012)
Because of the climate changes occurring across the planet, especially global warming, the different forms of agricultural soil use have attracted researchers´ attention. Changes in soil management may influence soil respiration and, consequently, C sequestration. The objectives of this study were to evaluate the long-term influence of liming on soil respiration and correlate it with soil chemical properties after two years of liming in a no-tillage system. A randomized complete block design was used with six replications. The experimental treatments consisted of four lime rates and a control treatment without lime. Two years after liming, soil CO2 emission was measured and the soil sampled (layers 0-5, 5-10, 10-20, and 20-30 cm). The P, Ca2+ e Mg2+ soil contents and pH and base saturation were determined. CO2 emission from soil limed at the recommended rate was 24.1 % higher, and at twice the recommended rate, 47.4 % higher than from unlimed soil. Liming improved the chemical properties, and the linear increase in soil respiration rate correlated positively with the P, Ca2+ and Mg2+ soil contents, pH and base saturation, and negatively with H + Al and Al3+ contents. The correlation coefficient between soil respiration rate and chemical properties was highest in the 10-20 cm layer.